Permethrin Insecticide Influence on Microorganisms Present in Surface Waters - Julia Sroczyńska; Urszula Guzik; Wojciech Smułek (Applied Sciences)
Agriculture and food production use very large amounts of plant protection products. These include insecticides, including pyrethroids, which belong to the third generation of pesticides. Although the ecotoxicity of these compounds is well known, their effect on environmental bacteria is still undefined. The aim of the presented research was to determine how permethrin can change the metabolism and surface properties of bacterial cells isolated from surface waters. Bacteria from water from a protected area (Snowy Ponds, Karkonosze National Park, Poland, 50°46′58″ N 15°33′47″ E) and a relatively polluted Kierskie Lake (52°27′10″ N 16°47′35″ E) next to the Poznań (Poland) agglomeration were compared. The obtained results showed that for the tested microorganisms, the toxic effect of permethrin is observed at 1000 ppm for water consortia and pure strains as well, except Bacillus thuringiensis KlaKry, which appeared to be resistant to the insecticide. What is more, the bacteria consortium from Kierskie Lake appeared to be more sensitive to insecticide, from the perspective of compound toxicity. At the same time, the metabolism assessed using EcoPlate™ showed that permethrin is not a factor determining the lower assimilation of various carbon sources, excluding carboxylic acids. Permethrin exposure also resulted in the decreased hydrophobicity of bacterial cells and increased permeability of their cell membrane. As a result, the obtained results show that if permethrin itself is not highly toxic, it can affect the properties of the cell wall and membrane. Consequently, it can potentially change the susceptibility of environmental bacteria to other xenobiotics.